Collaboration and Evolution of E-Commerce and Express Delivery Industry Supply Chain - Ying Xu; Xuemei Zhang; Jian Cao; Ya Chen; Xuhong Ye (Discrete Dynamics in Nature and Society)
Considering the contradictions between the electronic commerce (e-commerce) and its matching express delivery service, this paper investigates a supply chain regarding e-commerce and express delivery industry, in which collaborative operations of enterprises are discussed. The profitability and collaboration capability acting as order parameters and the rest of the influential resources including logistics, fund, information, and commodity are selected with their interrelations being examined based on servo theory of synergetics. Besides, evolutionary model of the e-commerce and express delivery industry is established and analyzed according to self-organization method of system dynamic theory to illustrate order parameters’ role in system evolution, and numerical analyses emerged to intuitively demonstrate the solutions. We conclude the work along with its results of significant references for investigating resource integrations by combining the two closely related businesses in an entire cooperative supply chain and providing guidelines for e-commerce and express delivery enterprises and industries in effective collaboration and system evolution.